Selanik ekonomisinde unutulmuş bir alan: tütün üretimi, ticareti ve reji (1883-1912) - (:unkn) unknown (My University, 2014)
XIX. yüzyıl Selanik ekonomisinde tütün son derece önemli bir tarımsal üründür. Selanik kırsalında üretilen tütünün ticareti, Selanik ekonomisinin uluslararası pazar- larla bağlantısını hızlandırmıştır. Tütün sektörüne XIX. yüzyılın son çeyreğinde Reji Şirketi dahil olduğunda başta tütün çiftçileri olmak üzere işçiler, tüccarlar ve şirketler yani Selanik piyasasındaki tüm aktörler bundan dolaylı olarak ve değişik biçimlerde etkilenmiştir. Bu makale Selanik’teki tütün ziraati ve ticaretinin Reji öncesi ve son- rasındaki durumunu, Selanik ekonomisindeki ayrıcalıklı yeri ile tütün fabrikasını ve Reji uygulamaları çerçevesinde ‘tütün kaçakçılığı’ meselesi ile Reji’nin kaçakçılığı sona erdirme çabalarından biri olan ‘kolculuk’ teşkilatı ve uygulamalarını incelemektedir.

Tobacco has been an important agricultural product for the economy of Sa- lonica in 19th century. Trade of tobacco, which were produced in Salonica countryside, strengthened the relationship between the Salonica economy and international markets. Regie Company participated in Salonica tobacco sector in the last quarter of the 19th century. All actors of tobacco sector, workers, merchants, other tobacco companies and especially tobacco farmers were affected -more or less- from the implementations of the Regie. This paper aims to discuss the production and trade of tobacco in Salonica before and after the Regie. The tobacco factory with its definite role in the economy of Salonica and tobacco smuggling will also be evaluated in the paper. Another issue of the paper is the activities of the “koldju” [guard] organization, which has been an instrument of the Regie to end the smuggling.
A forgetten field in the economy of salonica: tobacca production and trade, and the regie (1883-1912)
Keywords: Sanat; Kültürel Çalışmalar; Tarih; Edebiyat